The Up-Coming Crisis and the Banking Sector in the Baltic States - Mejra Festić; Sebastijan Repina; Alenka Kavkler (Swiss Journal of Economics and Statistics, 2009)
We tested for the significance of macroeconomic variables that condition nonperforming loan (NPL) ratios. The hypothesis of procyclicality between economic activity and improving NPL ratio in the Baltic States was proved. The increased economic activity improved the NPL ratio. Due to a high share of loans denominated in a foreign currency and the fact of productivity gains in the tradable sector, the appreciation of the real exchange rate contributed to an improvement in NPL ratio. The procyclicality of banking sector performance and high economic activities growth could be a signal of an economy overheating in the Baltics.
Keywords: F47; G15; G21; 330; cyclicality; non-performing loans; systemic risk; asset quality